Technology transfer performance and competitive advantage: Evidence from Yemen - Al-Abed M.S.; Ahmad Z.A.; Adnan M.A. (2023)
Most developing countries are relying more on technology transfer (TT) in different industries. Gaining the optimum benefits from implementing the TT process is the current issue in these countries. Based on the resource-based view (RBV) and knowledge-based view (KBV) perspectives, this paper aims to examine the relationship between technology transfer performance and competitive advantage. Using the quantitative research approach, the theoretical model and hypothesized relationships among the variables were tested based on empirical data collected from 514 managers and engineers selected randomly from nine oil and gas companies in Yemen. Structural equation modeling (SEM) was used for the purpose of analyzing the collected data. The study provides empirical evidence on the relationship between TT performance and competitive advantage, and it confirmed that TT performance is a strong predictor of competitive advantage. In addition, a set of practical implications is provided as well for the Government of Yemen, policy makers and managers especially those who are operating in the oil and gas industry in Yemen.